The Pharmacokinetic Effect of Itraconazole and Voriconazole on Ripretinib in Beagle Dogs by UPLC-MS/MS Technique [Corrigendum] - Wang H; Zhou C; Su Y; Gou K; Geng X; Qiu X (Dove Medical Press, 2023)
Wang H, Zhou C, Su Y, Gou K, Geng X, Qiu X. Drug Des Devel Ther. 2021;15:4865–4873. The authors have informed the journal that ripretinib was used in this study, not erdafitinib as indicated in parts of the paper. Namely, on page 4865, Abstract, Results section; page 4868, Animal Experiments and Pharmacokinetics Study sections; page 4872, Pharmacokinetics Effects and Conclusions sections. The authors have also advised on page 4867, Materials and Methods, Chemicals Materials section, third line from the bottom, the text “Itraconazole” should read “voriconazole”. The authors apologize for any confusion this may have caused.